1998
DOI: 10.1136/fn.78.3.f209
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of prenatally diagnosed anterior abdominal wall defects

Abstract: One hundred consecutive cases of confirmed anterior abdominal wall defect, identified prenatally in the Oxford Prenatal Diagnosis Unit over 11 years, were studied. Fifty nine per cent of cases were suspected omphaloceles and 41% suspected gastroschisis. Fifty four per cent of omphaloceles were accompanied by other defects compared with 5% of those with gastroschisis. Overall, 29% of fetuses with omphalocele had an abnormal karyotype, and of those with another abnormality identified on scan (excluding four case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
78
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 10 publications
17
78
3
2
Order By: Relevance
“…In an earlier study, 17 the mean maternal age was 20.4 years for gastroschisis, as compared to 28.0 years for the general population. Boyd et al 18 also found younger mothers in their gastroschisis group. Torfs et al 19 found the incidence of gastroschisis to be highest among mothers under 20 years old, with the incidence declining steeply with increasing maternal age; only 7% of mothers were over 29 years of age in their group.…”
Section: Discussionmentioning
confidence: 91%
“…In an earlier study, 17 the mean maternal age was 20.4 years for gastroschisis, as compared to 28.0 years for the general population. Boyd et al 18 also found younger mothers in their gastroschisis group. Torfs et al 19 found the incidence of gastroschisis to be highest among mothers under 20 years old, with the incidence declining steeply with increasing maternal age; only 7% of mothers were over 29 years of age in their group.…”
Section: Discussionmentioning
confidence: 91%
“…8,11,12,23 Lunzer et al 11 conducted interviews of parents of 10 gastroschisis survivors at 3 to 12 years of age. Two reported a learning disability, and one reported mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Developmental delay has been reported in 3 of 26 infants with gastroschisis as evaluated by parental questionnaire. 12 Comparing the results of previous studies to a contemporary cohort of infants with gastroschisis is problematic for several reasons. First, the outcome of cohorts that include all abdominal wall defects may be influenced by the comorbid conditions associated with different lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual associations of gastroschisis are limb-body wall defect syndrome (amniotic band syndrome), meningocoele, abnormal genitalia, umbilical cord abnormalities and gastrointestinal anomalies such as intestinal atresia, stenosis and malrotation (8,9) . In the literature, extra-intestinal anomalies are reported in 5% to 29% of infants with gastroschisis and include a variety of anomalies affecting the skeletal system, cardiovascular system and central nervous system (3,10,11) . In a study by Stoll C et al (2012) for associated malformations with gastroschisis, between 1979 and 2003 in 3,34,262 consecutive births, out of the 60 cases of gastroschisis, had associated malformations in 10 (16.6%) (9) .…”
Section: Discussionmentioning
confidence: 99%